An API management software quality metamodel based on square and GQM - Reboucas Dos Santos, Eder (2025)
With the widespread adoption of API in modern software ecosystems, the need for robust API management practices has become increasingly apparent. However, challenges persist in establishing a comprehensive framework for software product quality. To address this, this work introduces API-MQM, a tailored metamodel that leverages the ISO/IEC 25010 standard as a reference framework and employs the Goal-Question-Metric (GQM) paradigm. The design method adhered to ModelDriven Architecture (MDA) principles and emphasized the identification of API management capabilities as core quality requirements. To validate the proposal, both theoretical and empirical methods were conducted. The findings underscore the novelty and consistency of the proposed approach and outline directions for future research in the field.